Gratings in Structured Optical Fibres. (3rd November 2008) - Canning, John; Groothoff, Nathaniel; Cook, Kevin; Martelli, Cicero; Pohl, Alexandre; Holdsworth, John; Bandyopadhyay, Somnath; Stevenson, Michael
Abstract : Grating writing in structured optical fibres and their properties and applications are reviewed. To date, most gratings have been written in a straightforward manner into structured fibres containing a photosensitive germanosilicate step-index core. However, gratings have also been written directly into single material, structured silica fibres and into air-clad cores using two and higher-photon processes with both UV and near IR pulsed (nanosecond-femtosecond) light. Given the intrinsic-added functionality possible within a structured optical fibre, structured fibre gratings offer further capabilities for sensors, diagnostics, lasers, and devices.